A Bíblia na hipermídia: uma análise das interfaces de aplicativos para sites e dispositivos móveis - Silva, Adriana Ferreira da (2014)
This project aims to study the interfaces of biblical texts in digital media applications; it is considered that these projects take a hypermedia language. With the purpose of verifying what are the characteristics of communicational process present in devices and their interactions, that add in several languages the Bible textual content and other material of different nature. The research investigates the presence of the Bible in digital media, examining its characteristics in terms of hypermedia language on Web sites and applications used on mobile devices, such as, Tablet and Smartphone. The first part of the research carries out a Bible study in its historical course, starting from the oral tradition to the digital book, covering the interlacement that exists between the Scriptures and the historical evolution of the book and its transformations in roll formats and codex to digital media. The second part of this research focuses on the fine arts and the different media used in the biblical texts and where they were present in a pictorial form in Catholic Church history and are studied relations between the Catholic Church and the forms of communication of the Scriptures over the centuries from the papal documents and Dariva, Puntel and Zolin s researches are studied, in order to understand what is the position adopted by this institution in the face of changes in society, technological advances and, in particular, the Internet and its possibilities in spreading the Gospel. The third part of this research is devoted to the study of the Bible in hypermedia language and how these new media may extend the dissemination and understanding of the Scriptures in a refreshed and renewed way, using the features offered by this medium. In this stage sites and applications are analyzed, having in mind the potential of hypermedia language that combines features of hypertext (interactivity and usability) and multimedia (sound, texts, images and videos), based on Lucia Leão, Lucia Santaella, Pierre Lèvy e Julio César Freitas´s theories